ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL MATEMATIKA BERBENTUK CERITA PADA POKOK BAHASAN KELILING DAN LUAS LINGKARAN KELAS VIII SMP NEGERI 4 TOULUAAN - Enjel Watania; Jorry F. Monoarfa; Vivian E. Regar (CV. ADIBA AISHA AMIRA, 2022)
The purpose of this study is to analyze students' mistakes in solving problems in the form of stories about circumference and circle area. The type of research used is descriptive qualitative. This research was carried out in class VIII B of SMP Negeri 4 Touluaan, in the even semester of the 2021/2022 academic year. The subjects of the study numbered 13 students. Then given a test of the story questions around and the area of the circle to get data. The test results were then randomly selected 4 students based on different errors to interview. The data obtained are analyzed with the stages used are data reduction, data presentation and conclusion drawing. The results showed that out of the five questions given, most students made mistakes in answering story questions about the perimeter and area of the circle. Of the four types of problem solving polya the percentage of errors made sequentially with the largest to the smallest percentage is the error of re-examining with a percentage of 73.85%, the error of completing planning with a percentage of 46.15%, understanding the problem 40%, planning a solution 29.23%.